The Bromodomain and Extraterminal Protein Inhibitor Apabetalone Ameliorates Kidney Injury in Diabetes by Regulating Cholesterol Accumulation and Modulating the Gut Microbiota - Min Wang; Zhaohui Huang; Yonghong Zhu; Xin Li; He Sun; QiuLing Fan (Kidney International Reports)
Introduction: A US Food and Drug Administration–approved new bromodomain (BRD) and extraterminal (BET) bromine domain antagonist called apabetalone, which targets BRD4, has been shown to increase prebeta-1 high-density lipoprotein (HDL) particles, enhance apolipoprotein A-I in both humans and animals, and restore angiogenesis in experimental diabetes. Its action is not however fully known mechanistically. The objective of our research was to investigate the impact of apabetalone on renal damage linked to diabetic kidney disease (DKD). Methods: This research employed both pharmacological and genetic methods to examine the impact of apabetalone on db/db (BKS. Cg-leprdb/leprdb) mice and human tubular epithelial cells (HK-2). Results: Here, significant reductions in blood creatinine, urea nitrogen, and urinary albumin-to-creatinine ratio (UACR) levels, serum triglycerides (TGs) and serum total cholesterol (TC), as well as ectopic lipid droplet formation in renal tissue, were seen in the db/db mice following apabetalone therapy. Analysis of the gut microbiota revealed changes in its composition. Significantly, the proportion of Firmicutes to Bacteroidetes decreased, as well as Deferribacterota, indicating a positive influence on lipid metabolism. Untargeted metabolomic analysis indicated that the ABC transporter signaling pathway, implicated in cholesterol metabolism, was enriched. Moreover, peroxisome proliferator–activated receptor gamma (PPARγ)/liver X receptor (LXR)/adenosine triphosphate–binding cassette transporter A1 (ABCA1) protein, and mRNA level, as well as fibrosis-related marker proteins, fibronectin and collagen I were all improved by apabetalone. Conclusion: Therefore, we suggest that apabetalone showed significant antihyperlipidemic and antifibrotic effects, closely associated with alterations in the gut microbiota and cholesterol metabolism. The results of this investigation provide fresh perspectives on the processes that underlie apabetalone's effects in db/db mice.